PENGARUH PENGGUNAAN APLIKASI TIKTOK SEBAGAI MEDIA DAKWAH TERHADAP MAHASISWA DI ERA DIGITAL - Elsya Rahmalia Hidayat; Indriyani Dwi Putri; Maula Diah Liani; Muhamad Raihan Eka Putra; Surani Erni Morowati; Edi Suresman (Cahaya Ilmu Bangsa Institute, 2025)
The scope of technological development in the era of digitalization encourages the advancement of Islamic preaching media through modern digital platforms, which play a significant role in disseminating religious messages to the wider community. The TikTok application has become a significant platform in conveying religious messages through engaging and educational Islamic content that can build and develop religious understanding. This research aims to analyze the influence of using the TikTok application as a medium for preaching and to evaluate the effectiveness of the TikTok application as a means of spreading religious teachings among students. This research method uses a descriptive quantitative approach with survey methods and data collection in the form of questionnaires using Google Forms, targeting respondents who are students of the Universitas Pendidikan Indonesia. The research results show that the majority of students at the Universitas Pendidikan Indonesia have understood the use of the TikTok application and have made TikTok a medium for entertainment and information. The TikTok application is also considered effective in the process of disseminating religious knowledge through engaging and creative Islamic preaching content, thereby predominantly encouraging faster student understanding because the delivery of religious values is concise and easy to comprehend. However, in studying and understanding the religious content on the TikTok application, students need to understand the authenticity of the religious videos before sharing them. This is related to the critical awareness of students in responding to religious information disseminated on social media.